2022
DOI: 10.3390/atmos13040561
|View full text |Cite
|
Sign up to set email alerts
|

Improving Combustion Technology for Cooking Activities for Pollutant Emission Reduction and Carbon Neutrality

Abstract: Inefficient residential solid fuel combustion contributes significantly to ambient and indoor air pollutants. It consumes large quantities of fuel and produces harmful effects on health. Improvements in residential biomass cooking stoves have great potential for energy savings and emission reduction. This study presents an advanced biomass gasifier cooking stove to overcome the disadvantages of high-pollutant emissions from widely used stoves in China. The most innovative features of the stove are (1) negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…As previously explained, the role of a combustion process is vital to increasing the efficiency of domestic or industrial stoves and, subsequently, the sustainability of the process, reducing the amounts of pollutants released into the atmosphere, depending on factors such as biomass composition [21,22], previous conditions [23], stove design (including its evolution to improve performance) [24][25][26], or burning conditions [27][28][29]. Thus, some studies have previously dealt with this subject, as can be observed in Table 1.…”
Section: Novelty and Aim Of This Workmentioning
confidence: 99%
See 2 more Smart Citations
“…As previously explained, the role of a combustion process is vital to increasing the efficiency of domestic or industrial stoves and, subsequently, the sustainability of the process, reducing the amounts of pollutants released into the atmosphere, depending on factors such as biomass composition [21,22], previous conditions [23], stove design (including its evolution to improve performance) [24][25][26], or burning conditions [27][28][29]. Thus, some studies have previously dealt with this subject, as can be observed in Table 1.…”
Section: Novelty and Aim Of This Workmentioning
confidence: 99%
“…Finally, according to Figure 19, increasing the feeding rate showed similar results compared to the previously tested pellets, although a constant CO percentage, along with a lower increase in exhaust gas temperature when the pellet feed was at 125%, implied a higher yield for poplar pellet combustion. It should be noted that the behaviors of different kinds of biomass could be different in some aspects, such as carbon monoxide or carbon dioxide emissions, depending on their composition and disposition (raw, briquette, or pellet) [22,28,48]. Finally, according to Figure 19, increasing the feeding rate showed similar results compared to the previously tested pellets, although a constant CO percentage, along with a lower increase in exhaust gas temperature when the pellet feed was at 125%, implied a higher yield for poplar pellet combustion.…”
Section: Poplar Pellet Combustionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pakistan is a predominantly rural country having an average family size of five to seven members [84]. As per an estimate, about 90% of the rural and 50% of the urban population rely on biomass fuels in Pakistan [85][86][87]. However, this consumption was decreased for the population with improved income and economic conditions [88].…”
Section: Indoor Smoke Cox Voc and Pollutants From Household Energy So...mentioning
confidence: 99%